Composite particles for electrochemical devices, manufacturing method, electrodes for electrochemical devices, and electrochemical devices

Composite particles with a graft polymer structure and controlled formation methods address the issues of peel strength and springback in electrochemical devices, enhancing their durability and performance.

JP7613458B2Active Publication Date: 2025-01-15ZEON CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022503336
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-26
Filing Date
2021-02-19
Publication Date
2025-01-15
Estimated Expiration
2041-02-19

AI Technical Summary

Technical Problem

Existing electrochemical devices face challenges in achieving high peel strength of the composite material layer to the current collector, which affects durability, and are prone to springback, impacting cycle characteristics and high-temperature storage characteristics.

Method used

The use of composite particles containing a specific particulate polymer with a graft polymer structure and optional components like carboxymethyl cellulose and conductive additives, which are formed through controlled granulation processes, ensures strong adhesion and prevents migration, thereby improving peel strength and suppressing springback.

Benefits of technology

The composite particles enhance peel strength, reduce springback, and improve cycle characteristics and high-temperature storage performance of electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613458000001
    Figure 0007613458000001
  • Figure 0007613458000002
    Figure 0007613458000002
  • Figure 0007613458000003
    Figure 0007613458000003
Patent Text Reader

Abstract

Composite particles for an electrochemical element, the particles each comprising an electrode active material and a particulate polymer, wherein the particulate polymer includes a graft polymer, the graft polymer has a molecular structure including a specific backbone portion, and a graft portion that is a hydrophilic graft chain and is bound to the backbone portion, the content ratio of the graft portion of the graft polymer is 1-40 parts by mass with respect to 100 parts by mass of the backbone portion, and the angle of repose of the composite particles is 20-40°. In addition, provided are: a production method for the composite particles; an electrode that is for an electrochemical element and that contains the composite particles; and an electrochemical element comprising the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite particles for electrochemical devices, a production method, an electrode for electrochemical devices, and an electrochemical device. [Background technology]

[0002] Electrochemical elements such as lithium ion secondary batteries usually have electrodes such as positive and negative electrodes, and the electrodes usually have a current collector and a composite layer containing an electrode active material provided on the surface of the current collector. In many cases, the composite layer is formed by preparing a slurry containing materials constituting the composite layer and a solvent, applying the slurry to the surface of the current collector to form a layer of the slurry, and then drying the layer. Since the performance of the electrode greatly affects the performance of the electrochemical element, various studies have been made on the constituent materials of the composite layer. For example, various studies have been made on the materials constituting the composite layer in the electrodes of lithium ion secondary batteries. More specifically, various studies have been made on the binder, which is a material constituting the composite layer (for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-247050 A [Patent Document 2] JP 2005-78935 A (corresponding publication: U.S. Patent Application Publication No. 2005 / 064096) [Patent Document 3] International Publication No. 2011 / 024789 [Patent Document 4] International Publication No. 2019 / 039560 (Corresponding Publication: U.S. Patent Application Publication No. 2020 / 243861) Summary of the Invention [Problem to be solved by the invention]

[0004] One of the indicators of electrode performance is peel strength, that is, the strength of adhesion of the composite layer to the current collector. Peel strength affects the durability of the element, and for example, in a lithium ion secondary battery, the cycle characteristics and high-temperature storage characteristics can be improved by adopting an electrode with high peel strength. In order to improve the peel strength, it is known to use a block copolymer having an acidic functional group as a binder constituting the composite layer to improve the peel strength (Patent Document 4). However, there is a demand for a higher level of improvement in the peel strength of the binder.

[0005] It is also known that when a composite layer is formed by a process including a press operation using a block copolymer having an acidic functional group, a defect called springback may occur. That is, when an electrode having such a composite layer is manufactured and then stored in an environment of normal temperature and humidity, a defect that the film thickness of the composite layer increases may occur.

[0006] Therefore, an object of the present invention is to provide a component of an electrochemical element, which can improve the peel strength of an electrode, suppress the springback of the electrode, and improve the cycle characteristics and high-temperature storage characteristics of the electrochemical element, and a manufacturing method thereof.

[0007] A further object of the present invention is to provide an electrode for an electrochemical element, which has high peel strength, suppresses springback, and can improve the cycle characteristics and high-temperature storage characteristics of an electrochemical element, and an electrochemical element having improved cycle characteristics and high-temperature storage characteristics. [Means for solving the problem]

[0008] In order to solve the above problems, the present inventors have studied the process of manufacturing electrodes. In particular, when forming a composite layer by applying a slurry, the binder may migrate in the layer of the slurry, which may impair the peel strength. The inventors have considered adopting composite particles containing an active material and a binder instead of a slurry. By adopting the composite particles, the occurrence of migration can be avoided, but on the other hand, it becomes difficult to increase the adhesion between the current collector and the composite layer. In order to increase the adhesion, it is possible to adjust the components in the composite particles, such as by increasing the content of a block copolymer having an acidic functional group. However, according to the inventors' study, in this case, the flowability of the composite particles decreases, the homogeneity of the electrode decreases, and the cycle characteristics of the battery decrease. The inventors further studied these problems and found that the above problems can be solved by adopting composite particles containing a specific particulate polymer and having specific physical properties as a binder, and have completed the present invention. That is, the present invention is as follows.

[0009] [1] A composite particle for an electrochemical device comprising an electrode active material and a particulate polymer, The particulate polymer is a graft polymer, The graft polymer has a molecular structure including a trunk portion and a graft portion that is a hydrophilic graft chain bonded to the trunk portion, the trunk portion contains an aromatic vinyl block region composed of an aromatic vinyl monomer unit and a conjugated diene region composed of an aliphatic conjugated diene unit having 4 or more carbon atoms, and the content of the conjugated diene region in 100% by mass of the trunk portion is 50% by mass or more and 99% by mass or less; a content ratio of the graft portion in the graft polymer is 1 part by mass or more and 40 parts by mass or less with respect to 100 parts by mass of the trunk portion, The composite particle for an electrochemical device has an angle of repose of 20 to 40°. [2] The composite particle for an electrochemical device according to [1], further comprising carboxymethyl cellulose. [3] The composite particle for an electrochemical device according to [1] or [2], further comprising an acidic functional group-containing water-soluble polymer having a mass average molecular weight (MW) of 1,500 to 50,000. [4] The composite particle for an electrochemical device according to any one of [1] to [3], further comprising a conductive assistant. [5] The composite particle for an electrochemical device according to [4], wherein the conductive assistant contains either graphene or a carbon nanotube. [6] The composite particles for an electrochemical device according to any one of [1] to [5], wherein the composite particles have a volume average particle size of 10 μm to 200 μm. [7] A method for producing a composite particle for an electrochemical device according to any one of [1] to [6], comprising the steps of: A production method comprising: a step (A) of granulating a mixture containing an electrode active material and a particulate polymer. [8] The method according to [7], wherein in the step (A), an ammonium salt of a graft polymer is used as a material for preparing the mixture. [9] The mixture contains carboxymethyl cellulose, an acidic functional group-containing water-soluble polymer, or both of these, The method according to [7] or [8], wherein in the step (A), the ammonium salt of the carboxymethylcellulose, the ammonium salt of the water-soluble polymer containing an acidic functional group, or both of them are used as materials for preparing the mixture.

[10] An electrode for an electrochemical element comprising a current collector and a mixture layer provided on the current collector, The electrode for an electrochemical device, wherein the mixture layer contains the composite particle according to any one of [1] to [6].

[11] The electrode for electrochemical devices according to

[10] , wherein the mixture layer is a layer formed by pressure molding of the composite particles.

[12] The electrode for an electrochemical element according to

[11] , wherein the pressure molding is roll pressure molding.

[13] An electrochemical device comprising the electrode for an electrochemical device according to any one of

[10] to

[12] . Effect of the Invention

[0010] According to the present invention, it is possible to provide components of an electrochemical element, and a manufacturing method thereof, which can improve the peel strength of an electrode, suppress the springback of the electrode, and improve the cycle characteristics and high-temperature storage characteristics of an electrochemical element.

[0011] The present invention further provides an electrode for an electrochemical element that has high peel strength, suppresses springback, and can improve the cycle characteristics and high-temperature storage characteristics of an electrochemical element, as well as an electrochemical element with improved cycle characteristics and high-temperature storage characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the present invention will be described in detail with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples described below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.

[0013] In a polymer produced by copolymerizing multiple types of monomers, the ratio of structural units formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of that certain monomer to all monomers used in the polymerization of the polymer, unless otherwise specified.

[0014] The structure of a molecule or a part thereof, such as a polymerized unit, is not limited by its production method. For example, an aromatic vinyl monomer unit is a unit having a structure formed by polymerization of an aromatic vinyl monomer, but the aromatic vinyl monomer unit also includes a unit formed by a method other than the above and having the same structure as that formed by polymerization of an aromatic vinyl monomer.

[0015] [1. Composite particles] The composite particle of the present invention is a composite particle for an electrochemical device, which contains an electrode active material and a particulate polymer. The composite particles contain both the electrode active material and the particulate polymer in a single particle. By using such composite particles as a material for an electrochemical element, migration of the particulate polymer as a binder can be avoided. Specifically, by using the composite particles as a material for forming an electrode mixture layer without crushing or dissolving, the uniformity of the concentration of the particulate polymer relative to the electrode active material can be maintained in the electrode mixture layer.

[0016] [1.1. Electrode active material] The electrode active material contained in the composite particles can be appropriately selected from various active materials that can be used in the electrodes of electrochemical devices. For example, when the electrochemical device to be manufactured is a secondary battery, examples of the electrode active material include carbon materials and alloys, and carbon materials are preferred. A preferred example of the carbon material is graphite. The use of such a preferred material can improve the cycle characteristics of the resulting electrochemical device.

[0017] The content of the electrode active material in 100% by mass of the composite particles is preferably 90% by mass or more, more preferably 92% by mass or more, even more preferably 95% by mass or more, and preferably 99.5% by mass or less, more preferably 99% by mass or less, even more preferably 98.5% by mass or less. By having the content of the electrode active material be equal to or more than the lower limit, a high electrochemical device capacity can be obtained. By having the content of the electrode active material be equal to or less than the upper limit, good high-temperature storage characteristics can be obtained.

[0018] [1.2. Particulate polymer] The particulate polymer is a particle of a specific graft polymer. Hereinafter, this specific graft polymer may be referred to as graft polymer (G).

[0019] The graft polymer (G) has a molecular structure including a trunk portion and a graft portion bonded to the trunk portion. The trunk portion is usually a straight polymer chain, and the graft portion has a structure extending from the trunk portion in a branch-like manner. The trunk portion of the graft polymer (G) has a chain-like structure including an aromatic vinyl block region and a conjugated diene region. The graft portion of the graft polymer (G) is a hydrophilic graft chain.

[0020] The aromatic vinyl block region is a region containing aromatic vinyl monomer units as polymerization units. That is, the aromatic vinyl block region is a region having a structure in which aromatic vinyl monomer units are linked. However, one aromatic vinyl block region may contain, in addition to the aromatic vinyl monomer units, coupling sites such as those generated by a coupling reaction in the synthesis process.

[0021] The aromatic vinyl monomer unit is a unit having a structure formed by polymerization of an aromatic vinyl monomer. The aromatic vinyl monomer unit constituting one aromatic vinyl block region may be only one type or may be multiple types, but is preferably only one type. Examples of aromatic vinyl monomers include styrene, styrene sulfonic acid and its salts, α-methylstyrene, pt-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, vinylnaphthalene, and mixtures thereof. Among them, styrene is preferred. By having a unit formed by the preferred monomer, good high-temperature storage properties can be obtained.

[0022] The proportion of aromatic vinyl monomer units relative to 100% by mass of the trunk portion of the graft polymer (G) is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less. By having the proportion of aromatic vinyl monomer units equal to or more than the lower limit, good high-temperature storage properties can be obtained. By having the proportion of aromatic vinyl monomer units equal to or less than the upper limit, high peel strength can be obtained.

[0023] The conjugated diene region is a region containing, as a polymerization unit, an aliphatic conjugated diene unit having 4 or more carbon atoms. That is, the conjugated diene region is a region having a structure in which aliphatic conjugated diene units having 4 or more carbon atoms are linked together. However, one conjugated diene region may contain, in addition to the aliphatic conjugated diene units, a coupling site, such as one produced by a coupling reaction in a synthesis process.

[0024] The aliphatic conjugated diene unit having 4 or more carbon atoms is a unit having a structure formed by polymerization of an aliphatic conjugated diene monomer having 4 or more carbon atoms. The aliphatic conjugated diene monomer unit constituting one aliphatic conjugated diene region may be only one type or may be multiple types, but is preferably only one type. Examples of the aliphatic conjugated diene monomer having 4 or more carbon atoms include butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, and mixtures thereof. Among them, butadiene and isoprene are preferred, and butadiene is more preferred. By having a unit formed by the preferred monomer, good thermal stability can be obtained.

[0025] The ratio of the aliphatic conjugated diene monomer units having 4 or more carbon atoms to 100% by mass of the trunk portion of the graft polymer (G) is 50% by mass or more, preferably 60% by mass or more, more preferably 65% ​​by mass or more, and 90% by mass or less, preferably 80% by mass or less, more preferably 75% by mass or less. When the ratio of the aliphatic conjugated diene monomer units having 4 or more carbon atoms is equal to or more than the lower limit, high peel strength can be obtained. When the ratio of the aliphatic conjugated diene monomer units having 4 or more carbon atoms is equal to or less than the upper limit, good high-temperature storage properties can be obtained.

[0026] The grafted portion of the graft polymer (G) is a hydrophilic graft chain. Specific examples of the hydrophilic graft chain include a chain composed of a polymerization unit formed by polymerization of a hydrophilic monomer, a macromonomer, and a mixture thereof. The polymerization unit constituting the hydrophilic graft chain may be of only one type or may be of multiple types. When the graft polymer (G) has such a hydrophilic graft chain, it is possible to obtain an effect of suppressing springback.

[0027] Examples of hydrophilic monomers include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, 2-hydroxyethyl acrylate (β-HEA), vinyl sulfonic acid, and mixtures thereof. Among them, acrylic acid, methacrylic acid, itaconic acid, 2-hydroxyethyl acrylate, and mixtures thereof are preferred, and methacrylic acid is more preferred. In addition, as the macromonomer, a macropolymer containing an acidic group can be used. For example, it is preferred to use a macromonomer of a polycarboxylic acid polymer. By having a unit formed by the preferred monomer, a good springback suppression effect can be obtained.

[0028] The graft polymer (G) and other compounds (such as carboxymethylcellulose and water-soluble polymers containing acidic functional groups) that are components of the composite particles may have ionic groups in their molecular structures. Such ionic groups may exist in the form of free acids or free bases, anions or cations, or salts with any counter ions. For example, the hydrophilic graft chains of the graft polymer (G) may have carboxyl groups. Such carboxyl groups may exist in the form of free acid groups (i.e., -COOH), anionic groups (i.e., -COO - ), or in the form of a salt with any cation.

[0029] The content of the graft portion in the graft polymer (G) is 1 part by mass or more, preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and 40 parts by mass or less, preferably 20 parts by mass or less, more preferably 10 parts by mass or less, relative to 100 parts by mass of the trunk portion. By having the content of the graft portion be equal to or more than the lower limit, high peel strength can be obtained. By having the content of the graft portion be equal to or less than the upper limit, good cycle characteristics can be obtained.

[0030] The method for producing the graft polymer (G) is not particularly limited, and the graft polymer (G) may be produced by a known production method. For example, the graft polymer (G) may be produced by the production method described in WO 2019 / 039560.

[0031] The content of the particulate polymer in 100% by mass of the composite particle is preferably 0.2% by mass or more, more preferably 0.3% by mass or more, even more preferably 0.5% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less. By having the content of the particulate polymer be equal to or more than the lower limit, high peel strength can be obtained. By having the content of the particulate polymer be equal to or less than the upper limit, good cycle characteristics can be obtained.

[0032] 1.3. Optional Component of Composite Particles: Carboxymethylcellulose The composite particles of the present invention may contain carboxymethylcellulose as an optional component. From the viewpoint of obtaining the effect as a thickener, and from the viewpoint of obtaining good high-temperature storage properties and good cycle properties, the molecular weight of carboxymethylcellulose is preferably more than 50,000, preferably 100,000 or more. The upper limit of the molecular weight is not particularly limited, but may be, for example, 1,000,000 or less. The molecular weight may be a weight average molecular weight. The molecular weight may be measured by a measurement method such as GPC.

[0033] The content of carboxymethylcellulose in 100% by mass of composite particles is preferably 0.3% by mass or more, more preferably 0.4% by mass or more, even more preferably 0.5% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less. By having the content of carboxymethylcellulose be equal to or more than the lower limit, good high-temperature storage characteristics and good cycle characteristics can be obtained. By having the content of carboxymethylcellulose be equal to or less than the upper limit, good cycle characteristics can be obtained.

[0034] 1.4. Optional Component of Composite Particles: Water-Soluble Polymer Containing Acidic Functional Groups The composite particles of the present invention may contain an acidic functional group-containing water-soluble polymer as an optional component. A polymer is "water-soluble" when 0.5 g of the polymer is dissolved in 100 g of water at 25° C., the insoluble content is less than 1.0 mass %.

[0035] The acidic functional group-containing water-soluble polymer may be a polymer containing a polymerization unit formed by polymerization of a monomer having an acidic functional group and a polymerizable unsaturated bond. The acidic functional group-containing water-soluble polymer may be a polymer other than carboxymethylcellulose. Examples of such polymers include polyacrylic acid, polymethacrylic acid, polyitaconic acid, polymaleic acid, polyfumaric acid, poly2-hydroxyethyl acrylate (PHEA), poly2-hydroxyethyl methacrylate (PHEMA), and mixtures thereof. Among them, polyacrylic acid, polymethacrylic acid, polyitaconic acid, poly2-hydroxyethyl acrylate, and mixtures thereof are preferred, and polymethacrylic acid is more preferred. By adopting the preferred polymers, good cycle characteristics can be obtained.

[0036] The molecular weight of the acidic functional group-containing water-soluble polymer is 1500 or more, preferably 2500 or more, more preferably 5000 or more, and 50000 or less, preferably 30000 or less, more preferably 20000 or less. By having the molecular weight at or above the lower limit, high peel strength can be obtained. The molecular weight is a weight average molecular weight. The molecular weight can be measured by a measuring method such as GPC.

[0037] The content of the acidic functional group-containing water-soluble polymer in 100% by mass of the composite particle is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, even more preferably 0.03% by mass or more, and preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.3% by mass or less. By making the content of the acidic functional group-containing water-soluble polymer equal to or more than the lower limit, a good springback suppression effect can be obtained. By making the content of the acidic functional group-containing water-soluble polymer equal to or less than the upper limit, good cycle characteristics can be obtained.

[0038] [1.5. Optional component of composite particles: Conductive additive] The composite particle of the present invention may contain a conductive assistant as an optional component. The conductive assistant is a component for ensuring electrical contact between electrode active materials. Examples of the conductive assistant include carbon black (e.g., acetylene black, Ketjen Black (registered trademark), furnace black, etc.), single-layer or multi-layer carbon nanotubes (multi-layer carbon nanotubes include cup-stack type), carbon nanohorns, vapor-grown carbon fibers, milled carbon fibers obtained by crushing polymer fibers after baking, single-layer or multi-layer graphene, conductive carbon materials such as carbon nonwoven fabric sheets obtained by baking nonwoven fabric made of polymer fibers, and fibers or foils of various metals. These can be used alone or in combination of two or more. Among them, it is preferable that the conductive assistant contains carbon nanotubes (hereinafter sometimes referred to as "CNTs"). Here, CNTs usually tend to be easily aggregated and difficult to disperse. However, when the composite particle of the present invention contains an optional acidic functional group-containing water-soluble polymer, even a conductive assistant containing CNTs can be well dispersed.

[0039] [1.6. Properties of Composite Particles] The composite particles of the present invention have an angle of repose within a specific range. The angle of repose may be a value measured after leaving the composite particles for one week in an environment of a temperature of 25±3° C. and a relative humidity of 50±5%. More specific conditions for measuring the angle of repose may be as described in the examples of the present application.

[0040] The angle of repose of the composite particles of the present invention is 20° or more, preferably 22° or more, more preferably 25° or more, and 40° or less, preferably 38° or less, more preferably 35° or less. The angle of repose of the composite particles measured under the above measurement conditions is a value determined not depending on the amount of water absorbed by the composite particles, but depending on the type and content ratio of the particulate polymer and other components constituting the composite particles, as well as the shape and size of the composite particles, etc. According to the inventors' findings, when the angle of repose is equal to or more than the lower limit, high peel strength can be obtained. When the angle of repose is equal to or less than the upper limit, good cycle characteristics can be obtained.

[0041] The composite particle of the present invention preferably has a volume average particle diameter within a specific range. The volume average particle diameter is preferably 10 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, and preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 120 μm or less. By setting the volume average particle diameter to the lower limit or more, good high-temperature storage characteristics can be obtained, and the angle of repose can be easily adjusted to a value equal to or less than the desired upper limit. By setting the volume average particle diameter to the upper limit or less, good cycle characteristics can be obtained, and the angle of repose can be easily adjusted to a value equal to or less than the desired lower limit. The volume average particle diameter can be appropriately adjusted by selecting the material of the composite particle and adjusting the granulation conditions. The volume average particle diameter can be measured using a laser diffraction / scattering type particle size distribution measuring device (for example, manufactured by Nikkiso Co., Ltd., product name "Microtrac MT-3200II"). More specific measurement conditions can be as described in the examples of this application.

[0042] 2. Method for Producing Composite Particles The composite particles of the present invention can be produced by a production method including a step (A) of granulating a mixture containing an electrode active material and a particulate polymer. This production method will be described below as the production method of the composite particles of the present invention.

[0043] Specific examples of the granulation operation in step (A) include spray-drying granulation, fluidized bed granulation, rolling granulation, granulation by a solidification method, and granulation by freeze-drying. Among these, spray-drying granulation and fluidized bed granulation are preferred, and spray-drying granulation is particularly preferred. By adopting the preferred granulation method, composite particles having excellent characteristics such as cycle characteristics can be efficiently produced.

[0044] When spray-drying granulation is performed, a slurry composition containing the electrode active material, the particulate polymer, and optional components, if necessary, can be prepared as a mixture. Then, in step (A), this slurry composition can be used to perform granulation using an appropriate spray-drying granulation device. When fluidized bed granulation is performed, a mixed liquid containing components other than the electrode active material can be supplied to a fluidized bed in which the powder of the electrode active material is fluidized, and these can be mixed and granulated at the same time.

[0045] When preparing the mixture (including the mixture liquid in the previous stage of the mixture preparation), a salt of the graft polymer may be used as the graft polymer constituting the particulate polymer among the materials. In particular, since the hydrophilic graft chain of the graft polymer usually has an ionic group, when such a group is in a salt state with an appropriate counter ion, the preparation is easy. When the ionic group is an anionic group such as a carboxyl group, a salt with a counter cation may be used. Examples of preferred cations here include sodium ions, ammonium ions, lithium ions, potassium ions, and mixtures thereof. Among them, ammonium ions are particularly preferred. When ammonium ions are used as a material for preparing the mixture, the ammonium ions may volatilize in the granulation stage or in a subsequent process such as drying. As a result, the springback suppression effect can be further improved.

[0046] Similarly, when preparing a mixture containing carboxymethylcellulose, an acidic functional group-containing water-soluble polymer, or both of these, salts of these can be used as materials for preparation. When these have an anionic group such as a carboxyl group as an ionic group, examples of the counter cation include sodium ion, ammonium ion, lithium ion, potassium ion, and mixtures thereof. Among these, ammonium ion is particularly preferred. When ammonium ion is used as a material for preparing the mixture, the springback suppression effect can be further improved.

[0047] The particle size of the particulate polymer in the mixture may be preferably 0.01 to 1.0 μm on a volume average basis, and the particle size of the electrode active material in the mixture may be preferably 1.0 to 30 μm on a volume average basis.

[0048] In the case of spray drying granulation and fluidized bed granulation, the mixture is dried at an appropriate drying temperature in the granulation step. The drying temperature is preferably 160°C or higher, more preferably 170°C or higher, even more preferably 180°C or higher, and preferably 250°C or lower, more preferably 230°C or lower, and even more preferably 200°C or lower. By setting the drying temperature to the lower limit or higher, a good springback suppression effect, good cycle characteristics, and good high-temperature storage characteristics can be obtained. By setting the drying temperature to the upper limit or lower, high peel strength and good cycle characteristics can be obtained.

[0049] 3. Uses of composite particles The composite particles of the present invention are composite particles for electrochemical elements. That is, the composite particles of the present invention can be a material for a member constituting an electrochemical element. An example of an electrochemical element is a secondary battery such as a lithium ion secondary battery. An example of a member constituting an electrochemical element is an electrode such as a negative electrode. In the following, such an electrode will be described as an electrode for an electrochemical element of the present invention.

[0050] 4. Electrodes and their manufacturing methods The electrode for electrochemical elements of the present invention includes a current collector and a composite layer provided on the current collector, and the composite layer includes the composite particles of the present invention. The composite layer is preferably a layer formed by pressure molding of the composite particles. The pressure molding here is preferably roll pressure molding. More specifically, the composite particles or a mixed material containing the composite particles are supplied to the surface of the current collector in a particulate state without being crushed, dissolved, or the like, to form a layer of the composite particles, and the layer is pressed by a roll to a desired density, thereby forming the composite layer. In such a composite layer, migration during and after the manufacturing process is avoided, so that the uniformity of the concentration of the particulate polymer relative to the electrode active material can be maintained in the electrode composite layer. As a result, the peel strength is high, springback is suppressed, and the cycle characteristics and high-temperature storage characteristics of the electrochemical element can be improved.

[0051] 5. Electrochemical Devices The electrochemical device of the present invention comprises the electrode for electrochemical devices of the present invention. The electrochemical device of the present invention may comprise the electrode for electrochemical devices of the present invention as a positive electrode, a negative electrode, or both. In particular, it is preferable to comprise the electrode for electrochemical devices of the present invention as a negative electrode. By comprising the electrode for electrochemical devices of the present invention, the electrochemical device of the present invention can be an electrochemical device having improved cycle characteristics and high-temperature storage characteristics. EXAMPLES

[0052] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and can be modified and carried out as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.

[0053] In the following description, the units "%" and "parts" that represent amounts are by weight unless otherwise specified. Furthermore, the operations described below were carried out under normal temperature and pressure conditions unless otherwise specified.

[0054] In a polymer produced by polymerizing a plurality of kinds of monomers, the ratio of a monomer unit formed by polymerizing a certain monomer in the polymer is usually the same as the ratio (feed ratio) of the certain monomer to the total monomers used in the polymerization of the polymer, unless otherwise specified. In the examples and comparative examples, the volume average particle diameter of the particulate polymer, the volume average particle diameter and angle of repose of the composite particles, the peel strength and springback of the electrode mixture layer, and the cycle characteristics and high-temperature storage characteristics of the secondary battery were evaluated by the following methods.

[0055] [Volume average particle size of particulate polymer] The volume average particle diameter (D50) of the particulate polymer was measured using a laser diffraction particle size distribution analyzer (manufactured by Beckman Coulter, product name "LS-230"). Specifically, the particle diameter of the particulate polymer in an aqueous dispersion in which the solid content concentration of the particulate polymer was adjusted to 0.1 mass% was measured using the above-mentioned device, and the particle diameter at which the cumulative volume calculated from the small diameter side in the obtained particle size distribution (volume basis) was 50% was determined as the volume average particle diameter (μm).

[0056] [Volume average particle size of composite particles] The particle size distribution (volume basis) of the composite particles was measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT-3200II, manufactured by Nikkiso Co., Ltd.). Then, in the obtained particle size distribution, the particle size (median size) at which the cumulative volume calculated from the small diameter side was 50% was determined.

[0057] [Angle of repose of composite particles] Each of the composite particles produced in the examples and comparative examples was left for one week in an environment with a temperature of 25±3° C. and a relative humidity of 50±5%. After that, in a temperature and humidity controlled room with a temperature of 25±3° C. and a relative humidity of 50±5%, the composite particles were passed through a 250 μm sieve and dropped onto a repose angle measurement table through a funnel using a repose angle measurement device (Powder Tester PT-S), and the repose angle was measured when the shape of the mound became stable.

[0058] [Peel strength of electrode mixture layer] The negative electrode was cut into a rectangle of 100 mm in length and 10 mm in width to prepare a test piece. Cellophane tape (compliant with JIS Z1522) was attached to the surface of the negative electrode composite layer side of the test piece, and the cellophane tape was fixed to a test stand with the collector side facing up and the negative electrode composite layer side facing down. The test stand was set up so that the peel angle was 180°, and one end of the current collector of the test piece was pulled vertically at a pulling speed of 50 mm / min to peel it off, and the stress was measured. The measurement was performed three times, and the average value was calculated, which was taken as the peel strength and evaluated according to the following criteria. The higher the peel strength value, the better the adhesion between the negative electrode composite layer and the current collector. SA: Peel strength is 25N / m or more A: Peel strength is 20N / m or more and less than 25N / m B: Peel strength is 15N / m or more and less than 20N / m C: Peel strength is 10N / m or more and less than 15N / m D: Peel strength is 5N / m or more and less than 10N / m E: Peel strength is less than 5N / m

[0059] [Springback of negative electrode mixture layer] The springback of the negative electrode mixture layer was evaluated based on the density of the electrode mixture layer. Specifically, first, roll pressing was performed with the negative electrode mixture layer side of the prepared negative electrode as the roll side. The conditions of the roll pressing were a temperature of 25±3°C and a linear pressure of 1.8 t (ton) / cm. This roll pressing reduced the density of the electrode mixture layer to 1.70 g / cm. 3 The negative electrode was then left for one week in an environment with a temperature of 25±3°C and a relative humidity of 50±5%. The electrode mixture layer density (g / cm 3 ) was measured and evaluated according to the following criteria. A higher electrode mixture layer density after standing indicates that the negative electrode mixture layer does not spring back and is in a good condition. A: Electrode mixture layer density is 1.67 g / cm 3 End B: Electrode mixture layer density is 1.63 g / cm 3 More than 1.67g / cm 3 less than C: Electrode composite layer density is 1.59 g / cm 3More than 1.63g / cm 3 less than D: Electrode mixture layer density is 1.55 g / cm 3 More than 1.59g / cm 3 less than E: Electrode composite layer density is 1.55 g / cm 3 less than

[0060] [Cycle characteristics of secondary batteries] After injecting the electrolyte, the lithium ion secondary battery was left to stand at 25°C for 5 hours. Next, the battery was charged to a cell voltage of 3.65V at 25°C and a constant current of 0.2C, and then aged at 60°C for 12 hours in an open circuit. Then, the battery was discharged to a cell voltage of 3.00V at 25°C and a constant current of 0.2C. Then, the battery was CC-CV charged (upper cell voltage 4.20V) at a constant current of 0.2C, and CC discharged to 3.00V at a constant current of 0.2C. This charge and discharge at 0.2C was repeated three times at 25°C. Thereafter, 100 cycles of charge and discharge were performed at a cell voltage of 4.20-3.00V and a charge and discharge rate of 1.0C in an environment of 25°C, and the discharge capacity X1 of the first cycle and the discharge capacity X2 of the 100th cycle were recorded. From the discharge capacity X1 and the discharge capacity X2, the capacity change rate represented by ΔC'=(X2 / X1)×100(%) was calculated and evaluated according to the following criteria. The larger the value of this capacity change rate ΔC', the more excellent the cycle characteristics. SA: ΔC´ is 96% or more A: ΔC´ is 95% or more and less than 96% B: ΔC´ is 93% or more and less than 95% C: ΔC´ is 90% or more and less than 93% D: ΔC´ is 87% or more and less than 90% E: ΔC´ is less than 87%

[0061] [High temperature storage characteristics] The lithium ion secondary battery was charged to a cell voltage of 4.2 V by a constant current method of 0.5 C in an atmosphere of 25 ° C, and then discharged to 3.0 V, and the initial discharge capacity C0 was measured. Next, the lithium ion secondary battery was charged to a cell voltage of 4.2 V by a constant current method of 0.5 C in an atmosphere of 25 ° C. Then, this lithium ion secondary battery was stored in an atmosphere of 60 ° C for 3 weeks (high temperature storage). After high temperature storage, it was discharged to 3 V by a constant current method of 0.5 C in an atmosphere of 25 ° C, and the remaining capacity C1 after high temperature storage was measured. The capacity retention rate (%) = (remaining capacity C1 / initial discharge capacity C0) x 100 was calculated and evaluated according to the following criteria: A larger capacity retention rate indicates that the lithium ion secondary battery has better high-temperature storage characteristics. SA: Capacity retention rate is 93 or higher A: Capacity retention rate is 90% or more but less than 93% B: Capacity retention rate is 85% or more but less than 90% C: Capacity retention rate is 80% or more but less than 85% D: Capacity retention rate is 75% or more but less than 80% E: Capacity retention rate is less than 75%

[0062] Example 1 (1-1. Particulate polymer) (1-1-1. Block polymer solution) Into a pressure-resistant reactor, 233.3 kg of cyclohexane, 54.2 mmol of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as "TMEDA"), and 30.0 kg of styrene as an aromatic vinyl monomer were placed, and stirred at 40°C to obtain a mixture. To this mixture, 1806.5 mmol of n-butyllithium as a polymerization initiator was added, and the mixture was heated to 50°C and polymerized for 1 hour. The polymerization conversion rate of styrene after the polymerization reaction was 100%. Subsequently, while controlling the temperature to maintain 50-60°C, 70.0 kg of 1,3-butadiene as an aliphatic conjugated diene monomer was continuously added to the pressure-resistant reactor over 1 hour. After the addition of 1,3-butadiene was completed, the temperature was maintained at 50-60°C, and the polymerization reaction was continued for another 1 hour. The polymerization conversion rate of 1,3-butadiene was 100%. Next, 722.6 mmol of dichlorodimethylsilane was added as a coupling agent to the pressure-resistant reactor, and the temperature was controlled at 50 to 60°C. The coupling reaction was carried out for 2 hours to form a styrene-butadiene coupling block copolymer. Then, in order to deactivate the active terminal, 3612.9 mmol of methanol was added to the reaction solution and mixed well. Next, 0.05 parts of 4-[[4,6-bis(octylthio)-1,3,5-triazin-2-yl]amino]-2,6-di-tert-butylphenol (H1) as a hindered phenol-based antioxidant and 0.09 parts of 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (P1) as a phosphite-based antioxidant were added to 100 parts of this reaction solution (containing 30.0 parts of polymer component) and mixed to obtain a mixed solution. The resulting mixed solution was gradually dropped into warm water at 85 to 95° C. to volatilize the solvent and obtain a precipitate. The precipitate was then pulverized and dried with hot air at 85° C. to collect a dried material containing the block polymer. The recovered dried product was then dissolved in cyclohexane to prepare a block polymer solution with a block polymer concentration of 5.0%.

[0063] (1-1-2. Phase inversion emulsification) Sodium alkylbenzenesulfonate was dissolved in ion-exchanged water to prepare a 0.15% aqueous solution. Then, 1000 g of the block polymer solution obtained in (1-1-1) and 1400 g of the aqueous solution obtained above were charged into a tank and stirred to obtain a premixture. The premixture was then transferred from the tank to a high-pressure emulsifying and dispersing machine "LAB1000" (manufactured by SPXFLOW) using a metering pump and circulated (number of passes: 5 times) to obtain an emulsion in which the premixture was subjected to phase inversion emulsification. Next, the cyclohexane in the obtained emulsion was distilled off under reduced pressure using a rotary evaporator, and then the distilled emulsion was centrifuged at 7000 rpm for 10 minutes using a centrifuge (Hitachi Koki Co., Ltd., product name "Himac CR21N"), and the upper layer was removed to concentrate it. Finally, the upper layer was filtered through a 100 mesh wire screen to obtain a block polymer latex, which was an aqueous dispersion containing particulate block polymer.

[0064] (1-1-3. Graft polymerization and crosslinking) The block polymer latex obtained in (1-1-2) was diluted with distilled water to prepare a diluted latex. The dilution ratio was 850 parts of water per 100 parts of particulate block polymer (solid content equivalent). This diluted latex was placed in a nitrogen-substituted polymerization reaction vessel equipped with a stirrer, and heated to 30°C while stirring. In addition, a methacrylic acid dilution solution was prepared by mixing 8 parts of methacrylic acid as an acidic group-containing monomer and 15 parts of distilled water in a separate vessel. This methacrylic acid dilution solution was added to the diluted latex in the polymerization reaction vessel over 30 minutes. During the addition, the temperature was maintained at 30°C. As a result, 8 parts of methacrylic acid were added per 100 parts of block polymer. Further, a solution containing 7 parts of distilled water and 0.01 parts of ferrous sulfate (manufactured by Chubu Chelesto Co., Ltd., trade name "Frost Fe") as a reducing agent was prepared using another container. After the obtained solution was added to a polymerization reaction container, 0.5 parts of 1,1,3,3-tetramethylbutyl hydroperoxide (manufactured by Nippon Oil & Fats Co., Ltd., trade name "Perocta H") as an oxidizing agent was added, and the reaction was allowed to proceed at 30°C for 1 hour, and then further at 70°C for 2 hours to obtain a reaction product aqueous solution. The pH of this reaction product aqueous solution was adjusted to 8 by adding a 1.0 mass% aqueous solution of sodium hydroxide. Thereafter, the solid content concentration of the reaction product aqueous solution was adjusted to 40 mass% by heating and reduced pressure distillation to obtain a binder composition A for negative electrodes. In the binder composition A for negative electrodes, the polymerization conversion rate was 99%, and the volume average particle diameter of the particulate polymer was 0.5 μm.

[0065] (1-2. Slurry Composition for Negative Electrode) Into a planetary mixer, 97.4 parts of natural graphite (volume average particle size: 22 μm, theoretical capacity: 360 mAh / g) as a negative electrode active material, 1.0 part (solid content equivalent) of ammonium salt of carboxymethylcellulose (Daicel FineChem Co., Ltd., product number "DN-800H"), and 0.1 part (solid content equivalent) of ammonium polymethacrylate (mass average molecular weight: 10,000) as an acidic functional group-containing water-soluble polymer were added. Furthermore, the solid content concentration of the contents of the mixer was diluted with ion-exchanged water to 60%, and then kneaded for 60 minutes at a rotation speed of 45 rpm. Then, 1.5 parts of the negative electrode binder composition A obtained in (1-1-3) was added in solid content equivalent, and the contents of the mixer were kneaded for 40 minutes at a rotation speed of 40 rpm. Then, ion-exchanged water was added so that the viscosity (using a B-type viscometer, temperature: 25° C., rotor rotation speed: 60 rpm) became 1000±200 mPa·s, thereby preparing a slurry composition for the negative electrode.

[0066] (1-3. Composite particles for negative electrode) The negative electrode slurry composition obtained in (1-2) was supplied to a spray dryer (manufactured by Okawara Chemical Engineering Co., Ltd., product name "L-8i") and spray-dried using a rotating disk type Sharpedge atomizer (manufactured by Okawara Chemical Engineering Co., Ltd., diameter 65 mm) under conditions of a rotation speed of 25,000 rpm, a hot air temperature of 180°C, and a particle recovery outlet temperature of 90°C, to obtain composite particles for the negative electrode having a volume average particle diameter of 70 μm. The angle of repose of the obtained composite particles for a negative electrode was measured.

[0067] (1-4.Negative electrode) The composite particles for the negative electrode obtained in (1-3) were fed to a press roll (roll temperature 100°C, press line pressure 500 kN / m) of a roll press machine (Hirano Giken Kogyo Co., Ltd.'s "Oshi-Cut Rough Surface Hot Roll") using a quantitative feeder (Nikka Spray KV). A copper foil with a thickness of 15 μm was inserted between the press rolls, and the composite particles fed from the quantitative feeder were attached to the copper foil and pressed at a forming speed of 1.5 m / min. This resulted in a negative electrode comprising copper foil as a current collector and a negative electrode composite layer formed on one side of the copper foil. The mass per unit area of ​​the negative electrode composite layer was 13.0 mg / cm. 2 and the density is 1.65g / cm 3 It was. The peel strength and spring back of the obtained negative electrode were measured.

[0068] (1-5. Positive electrode) The planetary mixer is equipped with a lithium composite oxide material NMC532 (LiNi 0.5 Co 0.2 Mn 0.3 97 parts of acetylene (O2), 1 part of acetylene black (manufactured by Denki Kagaku Kogyo Co., Ltd., product name "Li-400") as a conductive additive, and 2 parts (solid content equivalent) of polyvinylidene fluoride (manufactured by Kureha Corporation, product name "#7208") as a binder were added and mixed. Furthermore, N-methyl-2-pyrrolidone (NMP) as an organic solvent was gradually added, and the mixture was stirred and mixed at a temperature of 25±3°C and a rotation speed of 25 rpm to obtain a slurry composition for a positive electrode with a viscosity (using a B-type viscometer. Temperature: 25±3°C, rotor: M4, rotor rotation speed: 60 rpm) of 3600 mPa·s. The obtained slurry composition for positive electrodes was applied to a 20 μm-thick aluminum foil current collector with a comma coater in an amount of 22.5±0.5 mg / cm. 2 The aluminum foil was then transported at a speed of 200 mm / min through an oven at 120° C. for 2 minutes and then through an oven at 130° C. for 2 minutes to dry the slurry composition on the aluminum foil, thereby obtaining a positive electrode raw sheet having a positive electrode mixture layer formed on the current collector. Thereafter, the positive electrode mixture layer side of the prepared positive electrode blank was roll-pressed in an environment at a temperature of 25±3°C to obtain a positive electrode mixture layer density of 3.20 g / cm 3 A positive electrode of 1000 nm was obtained.

[0069] (1-6. Separator) As a separator made of a separator substrate, a single-layer polypropylene separator (manufactured by Celgard, product name "Celgard 2500") was prepared.

[0070] (1-7. Lithium-ion secondary battery) A laminated cell (equivalent to an initial design discharge capacity of 300 mAh) was prepared using the negative electrode obtained in (1-4), the positive electrode obtained in (1-5), and the separator prepared in (1-6), and placed in an aluminum package and vacuum dried at 60°C for 10 hours. Then, a 1.0M LiPF6 solution (solvent: mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 3 / 7 (volume ratio), additive: containing 2 volume% vinylene carbonate (solvent ratio)) was filled as an electrolyte. Furthermore, in order to seal the opening of the aluminum package, the aluminum package was closed by heat sealing at a temperature of 150°C, and a lithium ion secondary battery was manufactured. Using this lithium ion secondary battery, the cycle characteristics and high-temperature storage characteristics were evaluated according to the above.

[0071] [Examples 2 to 3] In the preparation of the block polymer solution (1-1-1), the amounts of styrene and 1,3-butadiene added to the polymerization reaction were changed as shown in Table 1. Except for this, the same operations as in Example 1 were performed to obtain and evaluate particulate polymers, composite particles, negative electrodes, and lithium ion secondary batteries.

[0072] Example 4 In the graft polymerization and crosslinking of (1-1-3), a 1.0 mass% aqueous solution of ammonium was used instead of the 1.0 mass% aqueous solution of sodium hydroxide, and the same procedures as in Example 1 were performed to obtain and evaluate a particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery.

[0073] Example 5 In the graft polymerization and crosslinking of (1-1-3), 8 parts of acrylic acid was used instead of methacrylic acid, and the same operations as in Example 1 were performed to obtain and evaluate a particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery.

[0074] [Examples 6 to 7] In the graft polymerization and crosslinking of (1-1-3), the amount of methacrylic acid added was changed as shown in Table 1, and the same operations as in Example 1 were performed to obtain and evaluate particulate polymers, composite particles, negative electrodes, and lithium ion secondary batteries.

[0075] [Examples 8 to 9] In the preparation of the negative electrode slurry composition (1-2), the amount of ammonium polymethacrylate added was changed as shown in Table 2. The same procedure as in Example 1 was followed to obtain and evaluate particulate polymers, composite particles, negative electrodes, and lithium ion secondary batteries.

[0076] Example 10 In the preparation of the negative electrode slurry composition (1-2), 1.0 part (solid content equivalent) of sodium salt of carboxymethylcellulose (Daicel FineChem Corporation, product number "2200") was used instead of ammonium salt of carboxymethylcellulose, and the same operations as in Example 1 were used to obtain and evaluate a particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery.

[0077] [Examples 11-12] In the preparation of the composite particles for the negative electrode (1-3), the hot air temperature was changed as shown in Table 2, but the same procedure as in Example 1 was followed to obtain and evaluate a particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery.

[0078] Example 13 (13-1. Mixed liquid) 1.0 part (solid content equivalent) of ammonium salt of carboxymethylcellulose (Daicel FineChem Corporation, product number "DN-800H") as a thickener, 1.5 parts (solid content equivalent) of the binder composition A obtained in (1-1-3) of Example 1, and 45 parts of ion-exchanged water were added and mixed with a planetary mixer to obtain a mixed solution (I).

[0079] (13-2. Composite particles for negative electrode) Next, 97.4 parts of natural graphite (volume average particle size: 22 μm, theoretical capacity: 360 mAh / g) as a negative electrode active material was supplied to a fluidized bed granulator ("Agromaster AGM-25PJ" manufactured by Hosokawa Micron Corporation), and the mixed liquid (I) was sprayed over 10 minutes in an air flow at 80° C., and fluidized bed granulation was performed to obtain composite particles for the negative electrode having a particle size of 80 μm. The angle of repose of the obtained composite particles for a negative electrode was measured.

[0080] (13-3. Lithium-ion secondary batteries, etc.) A negative electrode and a lithium ion secondary battery were obtained and evaluated by the same procedures as in (1-4) to (1-7) of Example 1, except that the negative electrode composite particles obtained in (13-2) were used instead of the negative electrode composite particles obtained in (1-3).

[0081] Example 14 In the preparation of the composite particles for the negative electrode (1-3), the rotation speed of the atomizer was changed as shown in Table 2, but the same procedure as in Example 1 was followed to obtain and evaluate a particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery.

[0082] Example 15 A particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery were obtained and evaluated by the same procedures as in Example 1, except for the following changes. In the graft polymerization and crosslinking of (1-1-3), a 1.0 mass% aqueous solution of ammonium was used instead of the 1.0 mass% aqueous solution of sodium hydroxide. In the preparation of the negative electrode slurry composition (1-2), the amount of natural graphite used was changed from 97.4 parts to 97.2 parts. In preparing the negative electrode slurry composition (1-2), natural graphite, ammonium salt of carboxymethylcellulose, and ammonium polymethacrylate were added to a planetary mixer together with 0.2 parts of graphene (Sigma Aldrich, product number "Graphen powder") as a conductive additive.

[0083] Example 16 A particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery were obtained and evaluated by the same procedures as in Example 1, except for the following changes. In the graft polymerization and crosslinking of (1-1-3), a 1.0 mass% aqueous solution of ammonium was used instead of the 1.0 mass% aqueous solution of sodium hydroxide. In the preparation of the negative electrode slurry composition (1-2), the amount of natural graphite used was changed from 97.4 parts to 97.2 parts. In preparing the negative electrode slurry composition (1-2), natural graphite, ammonium salt of carboxymethylcellulose, and ammonium polymethacrylate were added to a planetary mixer together with 0.2 parts of carbon nanotubes (FT7010, manufactured by Cnano Corp.) as a conductive additive.

[0084] Example 17 A particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery were obtained and evaluated by the same procedures as in Example 1, except for the following changes. In the graft polymerization and crosslinking of (1-1-3), a 1.0 mass% aqueous solution of ammonium was used instead of the 1.0 mass% aqueous solution of sodium hydroxide. In the preparation of the negative electrode slurry composition (1-2), the amount of natural graphite used was changed from 97.4 parts to 96.9 parts. In preparing the negative electrode slurry composition (1-2), natural graphite, ammonium salt of carboxymethylcellulose, and ammonium polymethacrylate were added to a planetary mixer together with 0.5 parts of carbon nanotubes (FT7010, manufactured by Cnano Corp.) as a conductive assistant.

[0085] Comparative Example 1 (C1-1. Negative electrode) The negative electrode slurry composition obtained in Example 1 (1-2) was applied to the surface of a 15 μm-thick electrolytic copper foil current collector using a comma coater in an amount of 13±0.5 mg / cm 2 Thereafter, the copper foil coated with the negative electrode slurry composition was transported at a speed of 400 mm / min through an oven at a temperature of 130° C. for 4 minutes to dry the slurry composition on the copper foil, thereby obtaining a negative electrode raw sheet in which a negative electrode mixture layer was formed on a current collector. Thereafter, the negative electrode mixture layer side of the produced negative electrode blank was roll-pressed in an environment at a temperature of 25±3°C to obtain a negative electrode mixture layer density of 1.65 g / cm 3 A negative electrode of 1000 nm was obtained. The peel strength and spring back of the obtained negative electrode were measured.

[0086] (C1-2. Lithium-ion secondary battery) A lithium ion secondary battery was obtained and evaluated by the same procedures as in (1-5) to (1-7) of Example 1, except that the negative electrode composite particles obtained in (C1-1) were used instead of the negative electrode obtained in (1-4).

[0087] Comparative Example 2 In the preparation of the negative electrode (C1-1), the conditions for drying were changed to a speed of 400 mm / min in an oven at a temperature of 180° C. for 4 minutes, but the same procedures as in Comparative Example 1 were followed to obtain and evaluate a negative electrode and a lithium ion secondary battery.

[0088] Comparative Example 3 In the preparation of the composite particles for negative electrodes (1-3), the hot air temperature was changed as shown in Table 3, but the same procedures as in Example 1 were followed to obtain and evaluate particulate polymers, composite particles, negative electrodes, and lithium ion secondary batteries.

[0089] Comparative Example 4 Except for the following changes, the same procedures as in Example 1 were carried out to obtain and evaluate a particulate polymer, composite particles, a negative electrode, and a lithium ion secondary battery. In preparing the block polymer solution (1-1-1), the amounts of styrene and 1,3-butadiene added to the polymerization reaction were changed as shown in Table 3. In the preparation of the composite particles for the negative electrode in (1-3), the hot air temperature was changed as shown in Table 3.

[0090] Comparative Example 5 A particulate polymer, composite particles, anode, and lithium ion secondary battery were obtained and evaluated by the same procedure as in Example 1, except that the graft polymerization and crosslinking in (1-1-3) were not performed. That is, the block polymer latex obtained as a result of the phase inversion emulsification in (1-1-2) was used in an amount of 1.5 parts in terms of solid content in place of the binder composition A for anode in the preparation of the slurry composition for anode in (1-2) without going through the step of (1-1-3).

[0091] Tables 1 to 3 show the outlines and evaluation results of the examples and comparative examples.

[0092] [Table 1]

[0093] [Table 2]

[0094] [Table 3]

[0095] The meanings of the abbreviations in the table are as follows: Amount of active material: Amount of negative electrode active material used in producing the composite particles (unit: parts by mass). Amount of particulate polymer: Amount of particulate polymer used in producing composite particles (unit: parts by mass). Particulate polymer diameter: Volume average particle diameter (unit: μm) of the particulate polymer used in the production of the composite particles. St amount: Amount of styrene used in the production of the particulate polymer (unit: mass kg per 100 kg of total of styrene and butadiene). Bd amount: Amount of butadiene used in the production of the particulate polymer (unit: mass kg per 100 kg of styrene and butadiene in total). Graft species: the type of monomer used to form the graft chain in the production of the particulate polymer. MAA: methacrylic acid, AA: acrylic acid. Graft cation: The type of counter cation of the carboxyl group of the graft chain in the particulate polymer used in the production of the composite particle. Graft amount: the ratio of the graft portion to the trunk portion of the graft polymer (unit: parts by mass per 100 parts by mass of the block polymer of the trunk portion). Acidic polymer cation: The type of counter cation for the carboxyl group of the water-soluble polymer containing an acidic functional group used in the production of the composite particles. Amount of acidic polymer: Amount of water-soluble polymer containing an acidic functional group used in the production of composite particles (unit: parts by mass). Acidic polymer Mw: the mass average molecular weight of the water-soluble polymer containing an acidic functional group used in the production of the composite particles. CMC cation: The counter cation type of the carboxyl group of the carboxymethyl cellulose used in the production of the composite particles. CMC amount: Amount of carboxymethyl cellulose used in producing the composite particles (unit: parts by mass). Granulation method: Types of granulation methods used in the manufacture of composite particles. Spray drying: Spray drying granulation using a spray dryer. Fluidized bed: Fluidized bed granulation. (Coating): No granulation was performed since the electrode was formed by coating the slurry. Rotation speed: The rotation speed of the atomizer (unit: rpm) when spray drying granulation is performed. Granulation temperature: The temperature during granulation (unit: °C) when spray drying granulation or fluidized bed granulation is performed. Particle size: Volume average particle size of composite particles (unit: μm). Angle of repose: The angle of repose of a composite particle (unit: °). Weight: Mass per unit area of ​​the negative electrode composite layer (unit: mg / cm 2 ) Density: Density of the negative electrode (unit: g / cm 3 ). Peel: Evaluation result of peel strength. SB: Springback evaluation results. Cycle: Evaluation results of cycle characteristics. High temperature storage: Evaluation results of high temperature storage characteristics.

[0096] As is clear from the results of the Examples and Comparative Examples, when a negative electrode for a secondary battery and a secondary battery are manufactured using the specific composite particles defined in the present invention, all of the peel strength, springback suppression, cycle characteristics, and high-temperature storage characteristics are well-balanced and excellent. In contrast, when an electrode is formed without forming composite particles (Comparative Examples 1 and 2), when the angle of repose of the composite particles is outside the range defined in the present application (Comparative Examples 3 and 4), and when the particulate polymer constituting the composite particles does not satisfy the requirements defined in the present application (Comparative Example 5), all of the peel strength, springback suppression, cycle characteristics, and high-temperature storage characteristics are not well-balanced and excellent.

Claims

1. A composite particle for an electrochemical device comprising an electrode active material and a particulate polymer, The particulate polymer is a graft polymer, The graft polymer has a molecular structure including a trunk portion and a graft portion that is a hydrophilic graft chain bonded to the trunk portion, the trunk portion contains an aromatic vinyl block region composed of an aromatic vinyl monomer unit and a conjugated diene region composed of an aliphatic conjugated diene unit having 4 or more carbon atoms, and the content of the conjugated diene region in 100% by mass of the trunk portion is 50% by mass or more and 99% by mass or less; a content ratio of the graft portion in the graft polymer is 1 part by mass or more and 40 parts by mass or less with respect to 100 parts by mass of the trunk portion, The composite particle for an electrochemical device has an angle of repose of 20 to 40°.

2. The composite particle for an electrochemical device according to claim 1 , further comprising carboxymethyl cellulose.

3. 3. The composite particle for an electrochemical device according to claim 1, further comprising an acidic functional group-containing water-soluble polymer having a mass average molecular weight (MW) of 1,500 to 50,000.

4. The composite particle for an electrochemical device according to any one of claims 1 to 3, further comprising a conductive assistant.

5. The composite particle for an electrochemical device according to claim 4 , wherein the conductive assistant comprises either graphene or carbon nanotubes.

6. 6. The composite particle for an electrochemical device according to claim 1, wherein the composite particle has a volume average particle diameter of 10 μm to 200 μm.

7. A method for producing the composite particle for electrochemical devices according to any one of claims 1 to 6, comprising the steps of: A production method comprising: a step (A) of granulating a mixture containing an electrode active material and a particulate polymer.

8. The method according to claim 7, wherein in the step (A), an ammonium salt of the graft polymer is used as a material for preparing the mixture.

9. the mixture comprises carboxymethyl cellulose, a water-soluble polymer containing acidic functional groups, or both; The method according to claim 7 or 8, wherein in the step (A), the ammonium salt of carboxymethylcellulose, the ammonium salt of the water-soluble polymer containing an acidic functional group, or both of them are used as materials for preparing the mixture.

10. An electrode for an electrochemical element comprising a current collector and a composite layer provided on the current collector, An electrode for an electrochemical device, wherein the mixture layer comprises the composite particle according to any one of claims 1 to 6.

11. The electrode for an electrochemical device according to claim 10 , wherein the mixture layer is a layer formed by pressure molding of the composite particles.

12. An electrochemical device comprising the electrode for an electrochemical device according to claim 10 or 11.

Citation Information

Patent Citations

  • Production method of composite particle for electrode, manufacturing method for electrode and manufacturing method of electrochemical element, production device of composite particle for electrode, and manufacturing device of electrode and manufacturing device of electrochemical element

    JP2005078935A

  • Composite particle for electrochemical element electrode, electrochemical element electrode, and electrochemical element

    JP2013247050A

  • Composite particle with reduced particle size for electrochemical element electrode and method for producing composite particle with reduced particle size for electrochemical element electrode

    JP2015026432A

  • Method of manufacturing electrode for lithium ion secondary battery

    JP2015230748A

  • Method of making composite particle for electrode, method of making electrode, method of making electrochemical device, apparatus for making composite particle for electrode, apparatus for making electrode, and apparatus for making electrochemical device

    US20050064096A1